AN AUTOPSY BASED 05 YEAR RETROSPECTIVE STUDY OF DEATHS DUE TO SNAKEBITE IN CENTRAL INDIA REGION MADHYA PRADESH (Journal of Forensic Medicine & Toxicology, 2021)
This is a 05 years retrospective autopsy bases study of cases of fatal snake envenomation presenting to the mortuary of Mahatma Gandhi Memorial Medical College & M.Y. Hospital, Indore, from January 2016 to December 2020. The purpose of this study is to present the epidemiological pattern of snake poisoning in this region, as also to describe the clinical characteristic features. In our study, 58 cases (41 males & 17 females) of death due to snakebite were brought for medico legal post mortem examination to this department. Of these, maximum number of cases year wise, i.e. 17 cases; brought in the year of 2019. Age wise categorization shows equal no. of cases, i.e. 12 cases; in age groups 11-20, 21-30 & 31-40 years, followed by 11 cases in the age group of 41-50 years. The months of the rainy season, i.e. July & August, accounted for the maximum no. of cases i.e. 23. 70.68% of cases received hospitalization after getting bit by the snake. The area involved most commonly for the bite was the right upper limb (32.76%) followed by left lower limb (29.32%). In 89.66% of cases, only single site of bite was seen
Keywords: Snake envenomation; Hemorrhagic reactions; Cyanosis